A Europium(III) Complex with an Unusual Anion–Cation Interaction: A Luminescent Molecular Thermometer for Ratiometric Temperature Sensing - Outis, Mani (2022)
This work was supported by the Associated Laboratory for Sustainable Chemistry‐Clean Processes and Technologies – LAQV which is financed by national funds from FCT/MEC (UID/QUI/50006/2019) and co‐financed by the ERDF under the PT2020 Partnership Agreement (POCI‐01‐0145‐FEDER – 007265) The NMR spectrometers are part of The National NMR Facility, supported by Fundação para a Ciência e a Tecnologia (RECI/BBB‐BQB/0230/2012). We also thank to RNEM – Portuguese Mass Spectrometry Network, ref. LISBOA‐01‐0145‐FEDER‐022125, supported by FCT and Lisboa Regional Operational Programme (Lisboa2020). This work has been supported by Fundação para a Ciência e a Tecnologia through the contract n° IST‐ID/077/2018 (Bernardo Monteiro), SFRH/BD/120985/2016 (Mani Outis). Cláudia C. L. Pereira thanks to Fundação para a Ciência e a Tecnologia, MCTES, for the Norma transitória DL 57/2016 Program Contract.